Effect of Developmental Stimulation Education to Knowledge and Developmental Stimulation Practice of Pediatric By Parents at PAUD Kalisari Pasar Rebo - Hidayati, Syariefah; Hariyanto, Rohadi; Apriliawati, Anita; Sillehu, Sahrir; Acob, Joel Rey U.; Suparji, Suparji (Humanistic Network for Science and Technology (Address: Cemara street 25, Ds/Kec Sukorejo, Ponorogo, East Java, Indonesia 63453), 2017)
Parents sometime makes mistake to carry out their children because unknown about how to guide and parenting goodly. If this condition continues, growth and development of children will be delay. Guidance can be given by nurse to parents about step of development with simple counseling, interview and giving module, the parents will know what will happen and can fulfill the needs appropriate with childrenâs age. The aimed of this research to know effect of development stimulation education to knowledge and development stimulation practice in pediatric by parents at PAUD Kalisari Pasar Rebo. This research has used quasy experimental with non equivalent control group with thirty children were categorized into the intervention group (case 15) and the control group (N=15) by using consecutive sampling. The data was gathering instruments questionnaires which include demographic information, knowledge and observation of development practice by Develompent stimulation pre questionnaire, the government standard of instrument for parents and children. Hypothesis has analyzed by different mean test of two groups (intervention and control). Result of this research showed there was mean different between control and intervention group before and after intervention. Based on the result education about development stimulation should be given by nurse to parents in the community accourding to step of children development. Keywords: Education, Knowledge, Stimulation, Children, Development